Der Gebrauch der Jugendgewaltprävention Subjektivierungsformen eines Problemdiskurses - Kuglstatter, Verena (Gesellschaft der Unterschiede, 2017)
In what ways do specialists follow crime policy programs within the context of the prevention of juvenile violence and what consequences does that have for social work and juveniles?